Renal Involvement in Hospitalized Children with COVID-19 - Mahmoud Alhandi Omar Helal (16685388) (2023)
Background: Coronavirus disease 2019 (COVID-19), usually causes respiratory and gastrointestinal symptoms in children. While the clinical features range from upper respiratory tract infections to severe diseases. Kidney involvement in these children has been reported in different parts of the world, with different prevalence and acuity. To date, data are still accumulating to characterize kidney involvement in this disease and its impact on these children. Objective: We aimed to determine the prevalence of renal involvement in hospitalized children with COVID-19 in the state of Qatar and describe their clinical presentation and outcome. Methods: We retrospectively reviewed all children (age 0–14 years) with COVID-19 admitted to Hamad General Hospital, from March 1, 2020, to January 1, 2021. The diagnosis was confirmed by positive PCR results for the virus. We reviewed kidney involvement in these children at presentation, during hospitalization, and at 6 weeks follow-up. Results: A total of 2586 patients who were positive by PCR were reviewed, of which 584 were excluded due to missing data, and 1602 were completely asymptomatic at presentation. A total of 400 patients were then included in this study and were divided into two groups: patients without renal involvement (non-renal group) 282 patients (70.5%), and patients with renal involvement (renal group) 118 patients (29.5%). In the renal group, the median age was 16.7 months, and 90 patients (76.3%) were female. Fever was present in 107 patients (90.7%), and the median duration of hospitalization was 3.3 days. In this group, 84 patients (71.2%) presented with respiratory symptoms, and 34 patients (28.8%) presented with gastroenterological symptoms. The most frequent manifestation of renal involvement in these patients was microscopic hematuria, followed by leukocyturia, and acute kidney injury (AKI) was present in 14 patients (12%). During the reported period and follow-up of 6 weeks, children with AKI were at an early stage, and none of them required kidney replacement therapy. Conclusion: Kidney involvement in children with COVID-19 infection in our patients was noted in almost one-third of the patients and varied from urinary findings without any clinical symptoms to early-stage AKI. Electrolyte abnormalities with metabolic acidosis can present at presentation and require careful attention and management. Other information Published in: American Journal of Pediatrics License: http://creativecommons.org/licenses/by/4.0 See article on publisher's website: https://doi.org/10.11648/j.ajp.20230903.11